RPFdb: a database for genome wide information of translated mRNA generated from ribosome profiling - Xie, S. Q.; Nie, P.; Wang, Y.; Wang, H. W.; Li, H. Y.; Yang, Zhilong L.; Liu, Y. Z.; Ren, J.; Xie, Z. (My University, 2016)
Translational control is crucial in the regulation of gene expression and deregulation of translation is associated with a wide range of cancers and human diseases. Ribosome profiling is a technique that provides genome wide information of mRNA in translation based on deep sequencing of ribosome protected mRNA fragments (RPF). RPFdb is a comprehensive resource for hosting, analyzing and visualizing RPF data, available at www.rpfdb.org or http://sysbio.sysu.edu.cn/rpfdb/index. html. The current version of database contains 777 samples from 82 studies in 8 species, processed and reanalyzed by a unified pipeline. There are two ways to query the database: by keywords of studies or by genes. The outputs are presented in three levels. (i) Study level: including meta information of studies and reprocessed data for gene expression of translated mRNAs; (ii) Sample level: including global perspective of translated mRNA and a list of the most translated mRNA of each sample from a study; (iii) Gene level: including normalized sequence counts of translated mRNA on different genomic location of a gene from multiple samples and studies. To explore rich information provided by RPF, RPFdb also provides a genome browser to query and visualize context-specific translated mRNA. Overall our database provides a simple way to search, analyze, compare, visualize and download RPF data sets.
Citation: Xie, S. Q., Nie, P., Wang, Y., Wang, H. W., Li, H. Y., Yang, Z. L., . . . Xie, Z. (2016). RPFdb: a database for genome wide information of translated mRNA generated from ribosome profiling. Nucleic Acids Research, 44(D1), D254-D258. doi:10.1093/nar/gkv972
Keywords: In-Vivo; Seq; Reveals; Cells; Biochemistry & Molecular Biology